2011
DOI: 10.1007/s12199-011-0245-7
|View full text |Cite
|
Sign up to set email alerts
|

Binding of titanium dioxide nanoparticles to lactate dehydrogenase

Abstract: These findings, although based on a purified form of LDH, suggest that TiO₂ NPs bind to LDH, and consequently, TiO₂ NP-induced toxicity could be underestimated by the LDH activity assay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 9 publications
(16 reference statements)
0
11
0
Order By: Relevance
“…For example, LDHrelease showed significant decrease in membrane integrity at 0.1 g/L SiO 2 NP, but when the plates were centrifuged the only significant decrease in membrane integrity occurred at 1 g/L. It is possible that similar to TiO 2 NP [18], SiO 2 NPs bind LDH, and SiO 2 NP-LDH complexes were removed after plate centrifugation (in Figure 2(b)). Both PI and LDH release are indicators of membrane integrity; therefore, it was expected that LDH release will correlate with PI staining results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, LDHrelease showed significant decrease in membrane integrity at 0.1 g/L SiO 2 NP, but when the plates were centrifuged the only significant decrease in membrane integrity occurred at 1 g/L. It is possible that similar to TiO 2 NP [18], SiO 2 NPs bind LDH, and SiO 2 NP-LDH complexes were removed after plate centrifugation (in Figure 2(b)). Both PI and LDH release are indicators of membrane integrity; therefore, it was expected that LDH release will correlate with PI staining results.…”
Section: Discussionmentioning
confidence: 99%
“…Some of NP properties that were reported to interfere with viability plate-based assays are surface charge, agglomeration/aggregation, hydrophobicity, and optical or magnetic properties [15][16][17]. For example, it was reported that titanium dioxide NPs (TiO 2 NP; various size and concentrations) bind lactate dehydrogenase (LDH, indicator of cell viability) and alter assay readout [18]; copper NPs (Cu NP, 40 nm) and silver NPs (Ag NP, 35 nm) inactivate LDH [19]; gold NPs (Au NP; 10 nm) can absorb and traffic amine-containing dyes inside cells resulting in false positive results for membrane permeability assays [11]; single-wall carbon nanotubes (SWCNTs) interact with and alter the readout of WST-1 (2-(4-iodophenyl)-3-(4-nitrophenyl)-5-(2,4-disulfophenyl)-2H-tetrazolium), Coomasie Blue, Alamar Blue, Neutral Red, MTT, and plate-based cytotoxicity assays [20].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, there is a known binding activity between TiO 2 and lactate dehydrogenase, which is the commonly used cytotoxicity assay. 49,50 TiO 2 also caused noncellular reduction in the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay. 51 In the current study, WST-1 was selected as an indicator of metabolic activity assay because cell-free testing using NPs alone and the WST-1 reagent did not result in any artifacts or interferences, which suggests that WST-1 is a suitable indicator of cellular metabolism and, therefore, can be used as an indirect measure of cellular viability.…”
mentioning
confidence: 92%
“…As describes above, in vitro testing is essential to evaluate the biological activity of nanoparticles, however, it has been recently suggested that the physical and chemical features of nanoparticles can affect the results of in vitro experiments [3,4]. For example, results of in vitro tests are sometimes influenced by the physical properties of the nanoparticle suspension [5][6][7][8]. Therefore, characterization of the suspension is important for accurate interpretation of data produced by in vitro testing.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticle exposure can induce the secretion of inflammatory cytokines by cells or physically injure cellular membranes, resulting in LDH release into the surrounding medium. Thus, experimental methods that rely upon cytokine or LDH release as measurements of nanoparticle-induced toxicity may significantly underestimate particle effects [3,6]. Therefore, in vitro evaluation of nanoparticles should carefully account for these confounding effects.…”
Section: Introductionmentioning
confidence: 99%